Incidence of depression in young people during social isolation (Research, Society and Development, 2022)
Since the emergence of the pandemic, numerous consequences have been triggered for individuals in a collective and individual way, where physical and especially mental health problems stand out. Various prevention measures have been imposed in order to control the spread of the virus. Thus, the coronavirus was considered a threat and aggravating to public health. Therefore, this study is justified by the significant increase in the incidence of depression symptoms in young people during isolation. Therefore, the objective of this research is to highlight the main predisposing factors for depression in young people during the Covid-19 pandemic, as well as their psychosocial effects. Thus, in order to carry out this study, an integrative literature review was carried out, with the aim of gathering and analyzing the most recent published studies on the issue in question. As the main results found from the scientific evidence point out that emotional maladjustments such as anxiety and fear are directly linked to stress reactions, related to fake news and the large volume of information circulating daily in the media, often alarmist or sensationalists, directly activating an emotional trigger that produces a response to all the perceived maladjustment, thus concluding the importance of implementing innovative care strategies to face the psychological problems resulting from social isolation, with interventions that aim to minimize the effects of isolation and promote mental health through qualified listening and consultations with professionals trained in psychological consultations.